Influence of Cu film microstructure on MOCVD growth of BN. Issue 1726 (30th June 2015) - Snure, Michael; Vangala, Shivashankar; Shoaf, Jodie; Hu, Jianjun; Paduano, Qing
ABSTRACT: Boron nitride is of great interest as a 2 dimensional (2D) insulator for use as an atomically flat substrate, gate dielectric and tunneling barrier. At this point the most promising and widely used approach for growth of mono-to-few layer BN is metal catalyzed chemical vapor deposition (CVD). Bulk Cu foil has been the most popular metal substrate for growth of h-BN and graphene, as such there are well developed processes for substrate preparation and growth. As an alternative thin Cu films deposited on an insulating substrate have some advantages over foil, including more uniform thermal contact with substrate heater, better mechanical stability, transfer free processing, and selective area growth. However, Cu films deposited on SiO2 present their own unique problems like Cu SiO2 stability and small Cu grain size. Here we present results on the growth on few-layer BN by metal organic chemical vapor deposition (MOCVD) on Cu thin films on SiO2 /Si. We explore the effects of substrate preparation and annealing conditions on the Cu morphology in order to understand the impact on the BN. To minimize the effects of Cu SiO2 interdiffusion, we investigate the use of a Ni buffer layers. BN films were studied after transfer to SiO2 /Si films using Raman and AFM to determine the impact of Cu film microstructure on the morphology of few layer BN films.